Synergistic ferulic acid production from banana stem waste by co-culture - Kamaliah, Abdul Samad (2017)
Ferulic acid (FA) production using microbes has currently become extensive owing to its antioxidant properties. Both fungi and bacteria have been used in producing ferulic acid from agricultural waste. However, less work has been done on bacteria compared to fungi. Therefore, an appropriate bacterial co-culture fermentation technique using banana stem waste (BSW) as substrate was implemented to improve FA production. Soil microbes were isolated and preliminary study was performed to select the best bacterial strain. Subsequently, 26 type of bacterial co-cultures were formed and evaluated their ability dependent on FA production. Optimization of the FA production was conducted by employing response surface methodology using the selected co-culture as inoculum. A kinetic study was carried out to determine kinetic constants using Michaelis-Menten equation. Meanwhile, the enzyme assay was performed to investigate the mechanism release of FA by enzymatic hydrolysis. Ferulic acid production was accomplished through submerged fermentation and the sample was analyzed by HPLC to quantify the FA content. The result found that 5 out of 46 isolated bacterial strains were efficient in releasing FA from BSW. However, the highest production of FA was observed in co-culture A (Bacillus cereus CCM 2010, Bacillus pumilus SAFR-032 and Bacillus thuringiensis Bt407), followed by co-culture B (Bacillus cereus CCM 2010, and Bacillus thuringiensis Bt407). In improving the fermentation process, screening by fractional factorial design was performed and the result obtained presented four factors including pH, rotation rate, type of co-culture, and volume of inoculum have significant effects on FA production. Furthermore, rotation rate at 150 rpm and volume of inoculum of 5 % were found to be optimum in increasing FA yield up to 510.24 mg/kg within 24 h using bacterial co-culture B as an inoculum. Meanwhile, the kinetic constant of